Kebijakan Pendidikan MI: Perspektif Pendidikan Teman Sebaya - Lina Amalia; Siti Pitriani; Mizaniya Mizaniya; Ahmad Noviansah (Al - Azkiya : Jurnal Ilmiah Pendidikan MI/SD, 2020)
During early childhood, relationships with peers increased and spent a lot of time. One of the most important functions of peers is as a source of information and comparative materials outside the family environment, the peer environment is an important substitute for the family and the environment is also very supportive of how to fight a person therefore when the environment where a person is good then good behaviour. The research conducted is library research. This research does not have to be direct spaciousness but the data obtained is obtained from the source of literature or documentation. Data collection techniques using literature and documentation studies. Data validity checking technique using the triangulation method. Data analysis techniques using content analysis. Through peers, children get feedback on their abilities, evaluating what they do (whether better or less) than their peers.